STING induces early IFN-β in the liver and constrains myeloid cell-mediated dissemination of murine cytomegalovirus - Tegtmeyer, Pia-Katharina; Spanier, Julia; Borst, Katharina; Becker, Jennifer; Riedl, André; Hirche, Christoph; Ghita, Luca; Skerra, Jennifer; Baumann, Kira; Lienenklaus, Stefan; Doering, Marius; Ruzsics, Zsolt; et al. (Nature communications, 2019)
Cytomegalovirus is a DNA-encoded β-herpesvirus that induces STING-dependent type 1 interferon responses in macrophages and uses myeloid cells as a vehicle for dissemination. Here we report that STING knockout mice are as resistant to murine cytomegalovirus (MCMV) infection as wild-type controls, whereas mice with a combined Toll-like receptor/RIG-I-like receptor/STING signaling deficiency do not mount type 1 interferon responses and succumb to the infection. Although STING alone is dispensable for survival, early IFN-β induction in Kupffer cells is STING-dependent and controls early hepatic virus propagation. Infection experiments with an inducible reporter MCMV show that STING constrains MCMV replication in myeloid cells and limits viral dissemination via these cells. By contrast, restriction of viral dissemination from hepatocytes to other organs is independent of STING. Thus, during MCMV infection STING is involved in early IFN-β induction in Kupffer cells and the restriction of viral dissemination via myeloid cells, whereas it is dispensable for survival. Innate immune signaling pathways sense different microbial features and can elicit distinct yet overlapping immune responses. Here the authors dissect the contribution of these pathways to the response to MCMV infection and find that STING signaling is dispensable for host survival but crucial to restrict viral replication and dissemination via myeloid cells.